2019
DOI: 10.1111/ahe.12443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the correlation between adrenal gland dimensions and aortic diameter in healthy dogs

Abstract: In the present study, the relationship of normal adrenal dimensions with weight, aortic diameter, age and sex was evaluated. Moreover, a formula for estimating the normal dimensions of adrenal gland was provided. Thirty‐two intact adult dogs that were considered healthy based on history, physical examination, routine blood works and specific adrenal tests as well as absence of any abnormal ultrasonographic findings were included. Adrenal glands and abdominal aorta were imaged in the sagittal plane by ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…Additionally, other parameters such as adrenal area and circumference could be of interest for the assessment of adrenal gland size in different weight categories. 27 Finally, although body weight was not more than the double among the established body weight categories, the weight category that included large breed dogs (>20-40 kg) could had a higher amplitude than other weight categories. Therefore, further assessment of different weight categories in large-breed dogs could also be of interest.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, other parameters such as adrenal area and circumference could be of interest for the assessment of adrenal gland size in different weight categories. 27 Finally, although body weight was not more than the double among the established body weight categories, the weight category that included large breed dogs (>20-40 kg) could had a higher amplitude than other weight categories. Therefore, further assessment of different weight categories in large-breed dogs could also be of interest.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, further inclusion of older animals would be of value in future studies. Additionally, other parameters such as adrenal area and circumference could be of interest for the assessment of adrenal gland size in different weight categories 27 . Finally, although body weight was not more than the double among the established body weight categories, the weight category that included large breed dogs (>20–40 kg) could had a higher amplitude than other weight categories.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, adrenal length and height measured on the sagittal plane were significantly correlated with BW and showed less variation, particularly in small-breed dogs [ 9 , 16 , 17 ]. Moreover, the caudal pole of adrenal thickness measured on the sagittal plane was significantly correlated with gross appearance [ 24 ].…”
Section: Discussionmentioning
confidence: 54%
“…This factor contributes to the ambiguous normal reference of the adrenal gland in dogs, leading to misinterpretation. Several reports have shown that organ dimension-to-aorta (Ao) ratios are useful for assessing normal organ sizes in dogs, including kidneys [ 11 ], caudal vena cava [ 12 , 13 ], portal vein [ 14 ], and intra-abdominal lymph nodes [ 15 ], as well as the adrenal gland [ 16 , 17 ]. However, the adrenal dimension-to-Ao ratio in the normal adrenal gland, PDH, and adrenal tumors has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements obtained in the present study only correspond to adult non-lactating Holstein-Friesian cows. In dogs, a ratio comparing adrenal gland size and aortic diameter has recently been used to demonstrate the influence of weight on adrenal size and show the absence of any influence of sex or age on this ratio [31,32]. This should be explored in cattle, by considering different factors such as type of production (beef or dairy), breed, level of production, level of stress, etc.…”
Section: Discussionmentioning
confidence: 99%